2018
DOI: 10.7150/thno.20183
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis is exacerbated by chitinase-3-like-1 in amyloid precursor protein transgenic mice

Abstract: Although the important role of amyloid precursor protein (APP) in vascular diseases associated with Alzheimer's disease (AD) has been demonstrated, the underlying molecular mechanisms and physiological consequences are unclear. We aimed to evaluate vascular inflammation and atherosclerosis in Swedish mutant of human APP transgenic (APPsw-Tg) and ApoE-/-/APPsw-Tg mice. We also aimed to explore the mechanisms underlying any changes observed in these mice compared with non-Tg controls. Methods: The transgenic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 87 publications
(100 reference statements)
4
29
0
Order By: Relevance
“…Conversely, no relationship is found between CHI3L1 overexpression and survival in patients with cervical squamous cell carcinoma and liver cancer, while a negative correlation was observed between among patients bearing sarcoma. (from https://kmplot.com, http://www.cgga.org.cn) [177][178][179][180] Serum CHI3L1↑ → liver fibrosis Alcoholic liver disease 181,182 CHI3L1↑ → liver fibrosis Non-alcoholic fatty liver disease 183 CHI3L1↑ → liver fibrosis Bowel diseases IBD Fecal CHI3L1 → mucosal inflammation 184 and endoscopic activity 185 Colitis CHI3L1 binds to bacterial chitin-binding protein, 186,187 enhances bacterial adhesion and invasion, 60 activates Akt signaling 145 and IL-6-mediated STAT3 Phosphorylation 188 Cardiovascular Atherosclerosis CHI3L1↑ → coronary 189,190 and carotid 191 atherosclerosis severity↑, risk↑, 193 exacerbates atherosclerosis 192 Coronary artery disease Type 1 194 and type 2 195 diabetes CHI3L1↑…”
Section: Respiratory Diseases Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, no relationship is found between CHI3L1 overexpression and survival in patients with cervical squamous cell carcinoma and liver cancer, while a negative correlation was observed between among patients bearing sarcoma. (from https://kmplot.com, http://www.cgga.org.cn) [177][178][179][180] Serum CHI3L1↑ → liver fibrosis Alcoholic liver disease 181,182 CHI3L1↑ → liver fibrosis Non-alcoholic fatty liver disease 183 CHI3L1↑ → liver fibrosis Bowel diseases IBD Fecal CHI3L1 → mucosal inflammation 184 and endoscopic activity 185 Colitis CHI3L1 binds to bacterial chitin-binding protein, 186,187 enhances bacterial adhesion and invasion, 60 activates Akt signaling 145 and IL-6-mediated STAT3 Phosphorylation 188 Cardiovascular Atherosclerosis CHI3L1↑ → coronary 189,190 and carotid 191 atherosclerosis severity↑, risk↑, 193 exacerbates atherosclerosis 192 Coronary artery disease Type 1 194 and type 2 195 diabetes CHI3L1↑…”
Section: Respiratory Diseases Inflammationmentioning
confidence: 99%
“…Moreover, atherosclerosis is exacerbated by CHI3L1 in amyloid precursor protein transgenic mice. 192 Accordingly, CHI3L1 gene silencing could downregulate the expression of local proinflammatory mediators and inhibit plaques progression. 193 Additionally, CHI3L1 is an early inflammatory marker in diabetic subjects even in the presence of a low atherosclerotic background, 194,195 and is elevated in patients with peripheral arterial disease and diabetes or pre-diabetes.…”
Section: Urinarymentioning
confidence: 99%
“…Chitinase 3-like-1 (Chi3L1), also called a breast regression protein 39 (BRP-39) in mouse and YKL-40 in human, is known as a secreted glycoprotein and prototypic mammalian chitinase like protein [11,12]. Increased expression of Chi3L1 protein and mRNA have been shown in various disease models and states including rheumatoid arthritis schizophrenics, inflammatory bowel disease, chronic obstructive pulmonary disease, asthma, diabetes, and atherosclerosis [13][14][15][16][17][18][19], Especially, Chi3L1 expression has been found in a variety of cancer cells such as breast, lung, prostate, colon, rectum, ovary, kidney, breast, glioblastomas, and malignant melanoma [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Out of 2000 miRNAs that have been discovered in humans, miR-342-3p/-5p appear to have great potential to repress inflammation in atherosclerosis [ 15 , 16 ]. Additionally, current studies have shown miR-342-3p l to increase the cell survival, motility and proliferation of osteoclast precursors [ 17 ].…”
Section: Introductionmentioning
confidence: 99%